Pengaruh Sudut Sudu Turbin Jenis Taper Terhadap Tip Speed Ratio (TSR) dan Power Coefficient (CP) pada Turbin Angin Horisontal Berbasis Q-Blade - Aries Permana Tarigan, Roy; Ariawan, Radhi; Jauza Maulana, Adam; Al Khorni, Wais (Accurate: Journal of Mechanical Engineering and Science, 2022)
The utilization of wind energy as a power plant still needs to be improved by looking at the turbine performance, which is not always the same in different regional conditions. This study aims to determine the effect of the blade angle of the turbine on the tip speed ratio (TSR) and power coefficient (CP) by using a Q-Blade simulation. Q-Blade software can predict the value of the power generated at the blade rotation by comparing the CP and TSR values. The type of airfoil NACA 4412, taper blade, blade's numbers (4), blade radius (0.3 m), wind speed Â± 3.6 m/s were fixed variables in this study. The simulation generated a graph of the relationship between CP and TSR changed and a simulation image of the load distribution ensued in the blade geometry. The blade angle of 30 at the TSR number 5 produced the highest CP values, which was Â±0.4. The low loading value in the axis/rotor region, at a variation of the blade angle of 30, balances the centrifugal force on the rotating fluid. The centrifugal force produces thrust on the turbine so that the blade rotates with a high CP value in that area.